PSVIII-12 Effects of increasing iron dextran dosage at birth on hematological profile, growth performance, and tissue mineral concentrations of pigs in the nursery - Chevalier, Tyler B (J Anim Sci, 2020)
The objective of this experiment was to evaluate the blood profile, growth performance, and tissue mineral concentration during the nursery period in weanling pigs that received various dosages of iron at birth. A total of 70 crossbred pigs (weaning BW 6.36 ± 0.92) from 5 different injectable iron dosage treatments administered at birth (0, 50, 100, 200, and 300 mg iron from iron dextran) were used. Pigs were weighed at d 22 (weaning), 23, 24, 25, 29, 38, 44, and 52. Blood was collected from 10 pigs per treatment at the same times as above except for d 44 and analyzed for a complete blood count (CBC). A total of 3 pigs per treatment were euthanized on d 22, 38, and 52 to determine tissue mineral concentration. All pigs were fed a common nursery diet supplemented with 100 mg/kg Fe from ferrous sulfate. All data were subjected to ANOVA with the pig as the experimental unit. As injectable iron dosage at birth increased, hemoglobin concentration (Hb) increased at weaning (linear and quadratic: P < 0.05), to d 29 and then quadratically through (P < 0.05) d 38. Along with the other CBC measurements, Hb was similar between treatments at d 52. There was a quadratic response (P < 0.05) for ADG from d 22 to 52. Although by d 52, final BW peaked (quadratic: P < 0.05) for pigs receiving 100 mg iron. Iron concentration of the liver and spleen were greater (linear: P < 0.05) at weaning as iron injection dosage increased but was greater only in the liver at d 38 (P < 0.05) and the spleen at d 52 (P < 0.05). Results indicate that an iron injection administered shortly after birth is vital for proper growth and hematological functions during the nursery period. [Image: see text]